Ethnomedicines used in Trinidad and Tobago for reproductive problems - Lans Cheryl (BMC, 2007)
Abstract Background Throughout history women have tried to control or enhance their fertility using herbal remedies, with various levels of societal support. Caribbean folk medicine has been influenced by European folk medicine, either through the early Spanish and French settlers or through the continuous immigration of Spanish-speaking peoples from Venezuela. Some folk uses are ancient and were documented by Galen and Pliny the Elder. Methods Thirty respondents, ten of whom were male were interviewed from September 1996 to September 2000. The respondents were obtained by snowball sampling, and were found in thirteen different sites, 12 in Trinidad (Paramin, Talparo, Sangre Grande, Mayaro, Carapichaima, Kernahan, Newlands, Todd's Road, Arima, Guayaguayare, Santa Cruz, Port of Spain and Siparia) and one in Tobago (Mason Hall). Snowball sampling was used because there was no other means of identifying respondents and to cover the entire islands. The validation of the remedies was conducted with a non-experimental method. Results Plants are used for specific problems of both genders. Clusea rosea, Urena sinuata and Catharanthus roseus are used for unspecified male problems. Richeria grandis and Parinari campestris are used for erectile dysfunction. Ageratum conyzoides, Scoparia dulcis, Cucurbita pepo, Cucurbita maxima, Gomphrena globosa and Justicia pectoralis are used for prostate problems. The following plants are used for childbirth and infertility: Mimosa pudica, Ruta graveolens, Abelmoschus moschatus, Chamaesyce hirta, Cola nitida, Ambrosia cumanenesis, Pilea microphylla, Eryngium foetidum, Aristolochia rugosa, Aristolochia trilobata, Coleus aromaticus, Laportea aestuans and Vetiveria zizanioides. The following plants are used for menstrual pain and unspecified female complaints: Achyranthes indica, Artemisia absinthium, Brownea latifolia, Eleutherine bulbosa, Hibiscus rosa-sinensis, Eupatorium macrophyllum, Justicia secunda, Parthenium hysterophorus, Wedelia trilobata, Abelmoschus moschatus, Capraria biflora, Cordia curassavica, Croton gossypifolius, Entada polystachya, Leonotis nepetaefolia, Eryngium foetidum, Aristolochia rugosa, Aristolochia trilobata and Ambrosia cumanenesis. Conclusion Native Caribbean plants have been less studied that those from Africa, India and Europe. Chamaesyce hirta has scientific support but as a diuretic. Other plants with level 3 validity for reproductive issues are: Achyranthes indica, Coleus aromaticus, Hibiscus rosa-sinesis, Parthenium hysterophorus and Ruta graveolens. The non-experimental validation method can be used to advise the public on which plants are safe, effective and useful, and which are not; pending clinical trials. This is especially important since so few clinical trials are conducted on Caribbean plants.